Between becoming a historian and being a supervisor: the epistolary narrative of Carlos Roberto Antunes dos Santos to Cecilia Westphalen (1974-1976) - Machado, Daiane Vaiz [UNESP] (Univ Do Vale Do Rio Dos Sinos, 2018)
Writing on the self and the other, the epistolary narrative is a way of being seen by its addressee and a construction place of the interlocutor. As an observatory of sociability, the swarming of names of persons and institutions allows the analyst to establish connections, reconstitute structures of belonging and observe the functioning of social microcosms. This paper engages focuses on the daily life of a Brazilian historian in training. From the historiographical environment of Paris between 1974 and 1976, Carlos Roberto Antunes dos Santos, during his doctoral program, exchanged letters with Cecilia Westphalen, his colleague at the Federal University of Parana and Master's Degree supervisor at the same institution. With the epistolary narrative, from the point of view of the sender, we reflect on the cognitive process of learning and production, on the architecture of academic relations and on the social strategies of knowledge circulation. Thus, we wish to approach a way of becoming a historian and being a supervisor in the mid-1970s.
Keywords: Brazilian historiography; French historiography; epistolary narrative; historian's craft; graduate study